Accordion eulogies : a memoir of music, migration, and Mexico - Álvarez, Noé (Catapult, 2024)
"Growing up in Yakima, Washington, Noé Álvarez never knew his grandfather. Stories swirled around this mythologized, larger-than-life figure: that he had abandoned his family, and had possibly done something awful that put a curse on his descendants. About his grandfather, young Noé was sure of only one thing: That he had played the accordion. Now an adult, reckoning with the legacy of silence surrounding his family's migration from Mexico, Álvarez resolves both to take up the instrument and to journey into Mexico to discover the grandfather he never knew"--